2022
DOI: 10.3389/frwa.2022.801134
|View full text |Cite
|
Sign up to set email alerts
|

The Impacts of Climate Change on Land Hydroclimatology of the Laurentian Great Lakes Basin

Abstract: The freshwater resources of the Laurentian Great Lakes basin contribute significantly to the environment and economy of the region. With the impacts of climate change becoming more evident, sustainable management of the freshwater resources of the Laurentian Great Lakes basin is important. This study uses 36 simulations from 6 regional climate models to quantify trends and changes in land-area precipitation and temperature in two future periods (mid-century, 2035–2064 and end-century, 2065–2094) with reference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 104 publications
0
1
0
Order By: Relevance
“…In summary, our study has demonstrated that climate indices, which indicate broader atmospheric circulations, exert a discernible influence on CHL when combined with local factors. This integrated effect possess a significant threat to Lake Erie water quality, especially in the context of climate change (Byun & Hamlet, 2018;Carter & Steinschneider, 2018;Kayastha et al, 2022;Shrestha et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…In summary, our study has demonstrated that climate indices, which indicate broader atmospheric circulations, exert a discernible influence on CHL when combined with local factors. This integrated effect possess a significant threat to Lake Erie water quality, especially in the context of climate change (Byun & Hamlet, 2018;Carter & Steinschneider, 2018;Kayastha et al, 2022;Shrestha et al, 2022).…”
Section: Discussionmentioning
confidence: 99%